GAROTAS IN THE COUNTRY OF GOOD MANNERS: CIVILITY BETWEEN THE MANUALS AND THE MAGAZINES, AND BETWEEN THE LEGIBLE AND THE VISIBLE - Queiroz Campos, Daniela (História: Questões e Debates, 2018)
The papers discuss the column Girls of Alceu as textual and iconographic device that presents norms and precepts of civility. Roughly speaking, rules of civility are constant and encoded in so-called civility manuals. In Brazil during the first half of the twentieth century, one identifies numerous editions of these types of print. However, in the second half of that century, two elements concerning the circulation of these regulations on the national scene becomes notorious: the decrease of manuals' publication, and the mainstreaming of these norms in other print medias. Among books, soap-operas, novels, films, booklets also visualize the role of women's and varieties magazines in the dissemination of these good manner rules.